Las voces colombianas del exilio, la migración forzada y el retorno (2020)
Thousands of Colombian families have been forced to migrate abroad as a result of the armed conflict. Therefore, this research sought to give voice to the life narratives of nine Colombians who forcibly migrated from Colombia to other parts of the world. In particular, it sought to describe the expectations that those victims of the armed conflict, who have had to forcibly migrate, have regarding a program dedicated to their return. And specifically, analyze the way in which these preferences are related to: i. The temporary and political circumstances in which they left the country ii. Their experience as refugees in host countries iii. The emotional impacts suffered by forced cross-border migration. Starting from a qualitative methodology, semi-structured in-depth interviews were conducted with these victims of the conflict, as well as with two public officials who work on this matter. Thus, it was possible to raise a discussion between the narratives of the participants and some of the most important theories about exile, forced migration and return. As a result of this discussion, the present investigation found that both, victims abroad, as well as the public officials interviewed, believe that it is necessary for there to be psychosocial support, attention to basic needs and social relocation in a program that accompanies the return to Colombia.